Transformational Virtual Leadership and Marketing Team Performance in the E-Commerce Sector: An Integrated Review - Neila Aisha; Amelia Meisyah Putri; Aep Saefullah (LPPM Sekolah Tinggi Ilmu Ekonomi Ganesha, 2025)
The rapid advancement of digital technology has transformed leadership dynamics within e-commerce organizations operating under virtual work systems. This study aims to explore the impact of virtual transformational leadership on the performance of marketing teams using a descriptive qualitative approach. Conducted over three months (February–April 2025), the research involved direct observation and in-depth interviews with marketing teams from three digital companies. The analysis identified five dominant aspects—idealized influence, inspirational motivation, intellectual stimulation, individualized consideration, and active digital communication—that significantly enhance team creativity, collaboration, motivation, and loyalty. These findings reaffirm the relevance of transformational leadership theory in remote work settings and highlight the importance of developing digitally competent and empathetic leaders capable of sustaining engagement and productivity in virtual environments. The study concludes that responsive, human-centered leadership is essential for achieving sustainable success in the evolving e-commerce industry